Three new species and one new record of the fern genus Polystichum (Dryopteridaceae) from Vietnam - Lu, Ngan Thi; Zhang, Liang; Thanh, Nguyen Trung; Toan, Le Chi; Zhang, Li-Bing (Phytotaxa, 2023)
Three new species, Polystichum pseudodangii, P. xuansonense, and P. unicum, and a new record, P. omeiense, are described and reported here, respectively. These four species were found in limestone habitat in northern Vietnam, with the first species collected from Phu Tho Province and the rest from Ha Giang Province. Detailed descriptions, images, taxonomic notes, type information, examined specimens, distribution, and habitat are provided for the new species and new record.